Competitive Advantage through AI-Driven Digitalization: A Multi-Sectoral Study on Organizational Resilience and Innovation - Diaye, Mohamadou; Iwobi, Alex; Sor, Akor (Yayasan Gema Bina Nusantara, 2026)
This study investigates the strategic role of Artificial Intelligence (AI)-driven digitalization in securing a sustainable competitive advantage across diverse industrial sectors, specifically focusing on its impact on organizational resilience and innovation. In an era of unprecedented market volatility, the research utilizes a mixed-methods approach, combining a quantitative survey of 500 senior executives with qualitative expert interviews to examine how AI integration facilitates real-time decision-making and operational agility. The findings reveal that organizations with high digital maturity are significantly better equipped to withstand external economic shocks and are more capable of sustaining continuous innovation cycles. By comparing sectors such as manufacturing, healthcare, and finance, the study identifies that while AI implementation challenges vary by regulatory context, the fundamental driver of success remains the synergy between advanced technology and a flexible organizational culture. The results suggest that AI-driven digitalization shifts the competitive landscape from traditional efficiency models to dynamic, data-centric ecosystems. Ultimately, the research emphasizes that long-term resilience is achieved not just through technical adoption, but through a fundamental cultural transformation that integrates AI into the core strategic DNA of the enterprise, providing a roadmap for leaders to navigate the complexities of the fourth industrial revolution.